Ocular findings in asymptomatic patients with primary antiphospholipid syndrome. (December 2022) - Neto, Taurino SR; Neto, Epitacio DS; Balbi, Gustavo GM; Signorelli, Flavio; Higashi, Alex H; Monteiro, Mário Luiz R; Bonfá, Eloisa; Zacharias, Leandro C; Andrade, Danieli CO
Background: Primary antiphospholipid syndrome (PAPS) is characterized by the presence of antiphospholipid antibodies (aPL), repetitive fetal loss, and arterial/venous thrombosis and no association with other autoimmune rheumatic disease. Ocular involvement can also occur including retinal vascular thrombosis and neuro-ophthalmological manifestations, such as optic neuropathy and amaurosis fugax. Early detection of ocular changes is crucial to minimize functional loss. Purpose: To perform a multimodal evaluation, including the use of Optical Coherence Angiotomography (OCTA), in patients with PAPS without ocular complaints and compare with healthy individuals. Methods: We performed a complete structural and functional ophthalmological evaluation using OCTA and microperimetry exam in patients with PAPS, followed at a tertiary Rheumatology outpatient clinic. Results: We included 104 eyes of 52 subjects [PAPS without ocular complaints (N = 26) and healthy individuals (N = 26)]. Among PAPS patients, 21 were female (80.8%) and 21 (80.8%) were Caucasians. PAPS manifestations were venous (65.4%), arterial thrombosis (34.6%), and obstetrical (34.6%) and all of them had lupus anticoagulant. Ophthalmologic findings were more frequent in PAPS compared to healthy individuals (19.2% vs. 0%, p = 0.05). The most common retinal change was paracentral acute middle maculopathy (PAMM) (3 patients, 5 eyes), followed by drusen (1 patient, 2 eyes) and pachychoroid pigment epitheliopathy (PPE) (1 patient, 1 eye). Hypertension and hyperlipidemia were present in 100% of the PAPS patients with PAMM, while only six patients (26.1%) with PAPS without PAMM presented these two risk factors together ( p = 0.03). Conclusions: We provide novel evidence that approximately 20% of our asymptomatic PAPS patients without ocular symptoms have ophthalmologic findings that require early identification and careful surveillance focusing on minimizing systemic and vascular risk factors.